The Influence of Investment, Debt and Sales on Company Profitability in the Pharmaceutical Industryin Indonesia Stock Exchange - Indah Mursalini, Wahyu; Nasrah, Rasidah; Husna, Meryatul; Yadewani, Dorris; M. , Ilyas (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine and analyze the effect of investments, debt, and sales on the profitability of companies in the pharmaceutical industry listed on the Indonesia Stock Exchange for the period of 2012 to 2016. Investments are funds invested by investors into the company both directly and indirectly in order to gain profits. Debt is a loan fund obtained from inside and outside the company that is used to maintain the survival of the company. Sales are the results received for the sale of goods or services. Profitability will be obtained if investment, debt, and sales are managed properly. Management of investment, debt, and sales is a determining factor in the success of a company. Based on the results of the research, the influence between investment, debt, and sales on the company’s profitability is positive and significant. The results of this study support previous research, which says that debt and sales can increase the profitability of the company. For the next researcher, it is suggested to add other variables such as dividends, working capital, and economic growth.